Cross-Regional View of Functional and Taxonomic Microbiota Composition in Obesity and Post-obesity Treatment Shows Country Specific Microbial Contribution - Medina, Daniel A.; Li, Tianlu; Thomson, Pamela; Artacho, Alejandro; Pérez-Brocal, Vicente; Moya, Andrés (Frontiers in Microbiology, 2019)
Gut microbiota has been shown to have an important influence on host health. The microbial composition of the human gut microbiota is modulated by diet and other lifestyle habits and it has been reported that microbial diversity is altered in obese people. Obesity is a worldwide health problem that negatively impacts the quality of life. Currently, the widespread treatment for obesity is bariatric surgery. Interestingly, gut microbiota has been shown to be a relevant factor in effective weight loss after bariatric surgery. Since that the human gut microbiota of normal subjects differs between geographic regions, it is possible that rearrangements of the gut microbiota in dysbiosis context are also region-specific. To better understand how gut microbiota contribute to obesity, this study compared the composition of the human gut microbiota of obese and lean people from six different regions and showed that the microbiota compositions in the context of obesity were specific to each studied geographic location. Furthermore, we analyzed the functional patterns using shotgun DNA metagenomic sequencing and compared the results with other obesity-related metagenomic studies, we observed that microbial contribution to functional pathways were country-specific. Nevertheless, our study showed that although microbial composition of obese patients was country-specific, the overall metabolic functions appeared to be the same between countries, indicating that different microbiota components contribute to similar metabolic outcomes to yield functional redundancy. Furthermore, we studied the microbiota functional changes of obese patients after bariatric surgery, by shotgun metagenomics sequencing and observed that changes in functional pathways were specific to the type of obesity treatment. In all, our study provides new insights into the differences and similarities of obese gut microbiota in relation to geographic location and obesity treatments.